Hand washing practice among public primary school children and associated factors in Harar town, eastern Ethiopia: An institution-based cross-sectional study - Berhanu, Ashenafi; Mengistu, Dechasa Adare; Temesgen, Liku Muche; Mulat, Salie; Dirirsa, Gebisa; Alemu, Fekade Ketema; Mangasha, Adane Ermias; Gobena, Tesfaye; Geremew, Abraham (Frontiers in Public Health, 2022)
Background: Hand washing with soap and water reduces the risk of diarrheal episode by 28-48% and acute respiratory infection by 20-50%. However, there is limited evidence on hand washing practices among students in Eastern Ethiopia, particularly in Harari town. Therefore, this study aimed to determine hand washing practice among primary school students and associated factors in Harar town, Eastern Ethiopia. Methods: An institution-based cross-sectional study was applied among 670 students in Harar town from June 1 to 30, 2021. A multi-stage sampling was employed; 6 out of 20 schools were selected through simple random sampling, while eligible children from each school was selected by probability proportional to size sampling method. Data were collected using a pre-tested questionnaire with a face-to-face interview technique and via observation. The data were analyzed using SPSS software version 23. Binary and mult-variable analysis were used to determine the association between factors and outcome variable. Finally, a p-value of < 0.05 was considered to declare a statistically significant association. Results: A total of 670 participants were included in the study, of which 248 (37.0%) had washed their hands [95% CI: 33.3–40.06]. Being in grade 8 Adjusted Odd Ratio[AOR = 4.9; 95% Confidence Interval (CI): 2.28–10.52], living in an urban area [AOR = 3.49; 95% CI: 1.29–9.40], having role models (parents [AOR = 4.41; 95% CI: 1.79–10.86], teachers [AOR = 3.69; 95% CI: 1.39–8.81], and health professionals [AOR = 3.17, 95% CI: 1.17-8.63]), availability of hand washing facility [AOR=3.62; 95% CI: 1.57-8.34], access to soap and water [AOR= 2.89; 95% CI: 1.39-5.98] and being membership of Water Sanitation and Hygiene (WASH) club [AOR= 2.39; 95% CI: 1.41-4.03] were found to be significantly associated with hand washing practice. Conclusions: The Current study found that nearly a third of students practiced proper hand washing. Hand washing practice was influenced by students' grade level, residence, referents (role models for hand washing), presence of a hand washing facility, access to water and soap, and membership of WASH club. Therefore, the finding revealed that there is a need to improve hand-washing practices in schools by concerned agencies.